Bermudagrass Responses and Tolerance to Salt Stress by the Physiological, Molecular Mechanisms and Proteomic Perspectives of Salinity Adaptation - Maryam Noor; Ji-Biao Fan; Jing-Xue Zhang; Chuan-Jie Zhang; Sheng-Nan Sun; Lu Gan; Xue-Bing Yan (Agronomy, 2023)
Cynodon dactylon (L.) Pers. (commonly known as bermudagrass) is a member of the family Poaceae. It is a C4 grass that can grow annually and perennially with clone reproduction and seed-setting. It is not only used as forage but also as a weed in many crops. It grows along roadsides, in barren lands, irrigated lands, and seacoasts, where soil salinity is a major problem. Although bermudagrass is distributed worldwide, it shows limited growth under saline conditions. Under salt stress, the whole-plant growth is disturbed and the forage quality is compromised morphologically. At the physiological level, shoot development is affected owing to the resultant oxidative stress, although the total rate of photosynthesis is not greatly affected. Biochemical changes include a change in the K+/Na+ ratio; antioxidant enzymes such as superoxide dismutase and peroxide dismutase increase, while catalase activity slows down. The anatomical changes are visible as salt crystals on the leaf surface and salt glands on the mesophyll surface. In this paper, the morphological, physiological, biochemical, and proteomic mechanisms of bermudagrass under salt stress are discussed, drawing a study of several genes such as ECA4, RAN1, MHX1, psbA1, psbB1, psbP, and psbY at the molecular level. Therefore, the current review aims to understand how bermudagrass grows and adapts well under salt conditions.